2017
DOI: 10.1371/journal.pone.0169722
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Vibrio parahaemolyticus O3:K6 Strains That Have Been Isolated in Mexico Since 1998

Abstract: Vibrio parahaemolyticus is an important human pathogen that has been isolated worldwide from clinical cases, most of which have been associated with seafood consumption. Environmental and clinical toxigenic strains of V. parahaemolyticus that were isolated in Mexico from 1998 to 2012, including those from the only outbreak that has been reported in this country, were characterized genetically to assess the presence of the O3:K6 pandemic clone, and their genetic relationship to strains that are related to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…MLST is also a useful method for typing strains because of its reproducibility and comparability. The approach has been commonly used for analysis of V. parahaemolyticus isolates ( Guerrero et al, 2017 ). In this study, our isolates were grouped into five main clusters (I, II, III, IV, and V).…”
Section: Discussionmentioning
confidence: 99%
“…MLST is also a useful method for typing strains because of its reproducibility and comparability. The approach has been commonly used for analysis of V. parahaemolyticus isolates ( Guerrero et al, 2017 ). In this study, our isolates were grouped into five main clusters (I, II, III, IV, and V).…”
Section: Discussionmentioning
confidence: 99%
“…Until 2007, 22 serotypes had been traced to the pandemic clone based on these characteristics (Nair et al, 2007 ). In recent years, an increasing number of pandemic serotypes have been reported to be widely distributed in countries across four continents (Asia, Europe, the Americas and Africa) (Ansaruzzaman et al, 2008 ; Ottaviani et al, 2010 ; Powell et al, 2013 ; Li et al, 2014 ; Velazquez-Roman et al, 2014 ; Guerrero et al, 2017 ), suggesting that these pandemic serotypes pose a mounting public health threat. This threat calls for higher surveillance of the pandemic clone to reduce illnesses.…”
Section: Introductionmentioning
confidence: 99%
“…Six O3:K6 V. parahaemolyticus strains (Table 1 ), described as belonging to sequence type 3 (ST3) by multilocus sequence typing (MLST) [ 15 ], were sequenced for the present study. Genomic DNA from a single colony of each strain was extracted using the cetrimonium bromide (CTAB) method.…”
Section: Methodsmentioning
confidence: 99%
“…Brazil presented the lowest incidence of infections, with only 18 clinical cases reported from 2001 to 2002 [ 14 ]. Guerrero et al [ 15 ], found that the O3:K6 clinical strain had been isolated in Mexico by INDRE (Mexican Epidemiological Institute) between 1998 to 2009, in different states, and Revilla-Castellanos et al [ 16 ] identified the strain in 2012 among hull biofouling samples from a ship with Japanese provenance. O3:K6 strains were also isolated in 2004, from the only recorded outbreak in Mexico, which resulted in more than 1200 clinical cases [ 17 ].…”
Section: Introductionmentioning
confidence: 99%